Community safety through partnership tasking. (1st March 2011) - Mccall, M; Hayes, D
Abstract : Partner Agencies Include Fife Community Safety Partnership Fife Police Fire Service RSL's Victim Support Fife NHS Fife Fife Council Education/Social Work Service Environmental Services Housing and Local Services. The establishment of the Safer Neighbourhoods Tasking Group and the adoption of a multi-agency tasking approach, involving key local services, combined with effective community engagement has led to greatly improved community perceptions and begun to address the links between antisocial behaviour and longer term problems of health inequalities and community cohesion. Monthly meetings use a tasking approach, based on the police National Intelligence Model, to gather and manage information and make informed and effective decisions. Community and partnership intelligence is key to the tasking process. A tactical assessment document is produced containing data from all partner agencies. Allocated tasks cover a range of issues, including youth disorder, under age drinking, noise nuisance, neighbour nuisance, secondary fires and hate crime. The partnership tasking model encourages a move away from business as usual by providing effective joint approaches and early interventions to reduce the risk of problems escalating and by providing support to victims and offenders. Outcomes: Vandalism offences – 30% reduction Secondary fires – 23% reduction Street disorder – 26% reduction Antisocial behaviour (ASB) offences – 9% reduction ASB incidents – 30% reduction Noise nuisance incidents – 43% reduction Public Perception Rubbish and litter (down 38%) Graffiti and vandalism (down 35%) Assaults/attacks (down 33%) Young people hanging about (down 33%) Work is now underway to roll out the approach to other areas in Fife.